On the observability of the early universe - Bersanelli, Marco (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2018)
In the framework of contemporary cosmology, the age-old aspiration to inquire the outer limits of the universe translates into our effort to observe the initial stages of cosmic history. Thanks to a fortunate combination of astronomical circumstances, and pushing mm-wave technology to its limits, today we are able to image the early universe in great detail, back at a time (t ∼ 380,000 yr) when cosmic age was only 0.0027% of its present value. The state of the art in the field has been set by the ESA Planck mission, launched in 2009, dedicated to precision measurements of the cosmic microwave background (CMB). Planck observed the full sky for 4 years in a wide frequency range, reaching μK sensitivity both in temperature and polarization. The latest results, published by the Planck Collaboration in 2018, are in exquisite agreement with the simplest 6-parameter ΛCDM model and constrain the main cosmological parameters with percent-level accuracy. Furthermore, the Planck data yield insight on the very early universe (t ∼ 10-35s), opening the way to a new generation of experiments searching for the possible signatures of primordial gravitational waves in the CMB polarization pattern.